Answers

2015-02-06T16:14:26+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
HCF = (x-y)
LCM of two quantities is xy times of their HCF
so LCM = xy(x-y) 

one number = x²-xy = x(x-y)
let the other number be a.

since product of numbers is equal to product of their LCM and HCF

 product\ of\ numbers=HCF*LCM\\ \\(x(x-y))*a=(x-y)(xy(x-y))\\ \\(x(x-y))*a=xy(x-y)^2\\ \\a=  \frac{xy(x-y)^2}{x(x-y)} \\ \\a=\boxed{y(x-y)}

So other number is y(x-y)
1 5 1
2015-02-07T01:16:38+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Product of two nos=HCF X LCM
x²-xyX 2nd no= (x-y)Xxy(x-y)
⇒2nd no=(x-y)(x-y)xy/x(x-y)
⇒2nd no=xy-y²
1 4 1